THE THERMAL STABILITY OF THE HETEROMETALLIC COMPLEX [ZN2CR2(NCS)4(DEA)2(HDEA)2]·4DMSO: UDC 541.49 + 536-33 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The thermal stability of the heterometallic complex [Zn2Cr2(NCS)4(Dea)2(HDea)2]∙4DMSO (H2Dea = diethanolamine, DMSO = dimethylsulfoxide) in air and under argon atmosphere was studied. The thermolysis in air was shown to result in the formation of the mixture of Cr2O3 and ZnCr2O4.
Keywords: -